Pengembangan Aplikasi Pariwisata Kotawaringin Barat Berbasis GIS Menuju Smart Tourism City - Gregorius Anung Hanindito; Jamaludin Dwi Laspandi (Jurnal Media Infotama, 2023)
West Kotawaringin Regency is located in Central Kalimantan Province, Indonesia. This regency has great potential in its tourism. The local government support the tourism by prioritizing the tourism in the local goverment's program, alongside with infrastructure and agriculture. One of the famous tourist attractions in West Kotawaringin Regency which attracts many visitors both local and foreign visitors is Tanjung Puting National Park (TPNP). TPNP is the natural habitat for the Orang Utan, the indigineous and protected fauna from Kalimantan and some areas of Sumatra. Besides TPNP, West Kotawaringin Regency also has some cultural attractions since this regency has a kingdom named The Sultanate of Kutaringin. This regency also has another tourism attractions such as beach attractions, river cruise, souvenir shopping, and local culinary attractions. Although this regency has various tourist attractions, Kotawaringin Barat Regency has not conducted a good tourism governance. At the moment, many tourists just focused only in visiting TPNP. This happened because of their lacking information about the other tourist attractions that this regency serves. Because of this problem, this study is aimed to create a GIS tourism application that is able to provide information to all potential tourists about various attractions that the the regency has. It is hoped that this application will make the tourist visits in the West Kotawaringin area will become more evenly distributed to make West Kotawaringin a Smart Tourism City which will lead to economic equality for the community and tourism activists.